Informal employment in emerging and transition economies - Fabián Slonimczyk (IZA World of Labor, 2014)
In developing and transition economies as much as half the labor force works in the informal sector. Informal firms congest infrastructure and other public services but do not contribute to financing them. Informal workers are unprotected against such negative shocks as ill-health. Reducing informality requires better enforcement, more reasonable regulation, and economic growth.
Keywords: J46; 330; informality; shadow economy; mobility; exclusion